2003
DOI: 10.1034/j.1399-5448.2003.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between glycemic control, ethnicity and socioeconomic status in Hispanic and white non-Hispanic youths with type 1 diabetes mellitus

Abstract: This study suggests that Hispanic youths with type 1 diabetes may be at greater risk for poor glycemic control because of their lower socioeconomic status rather than their ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
116
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 12 publications
14
116
2
3
Order By: Relevance
“…Ethnicity had a greater impact than SES on HbA 1c , and moderate to severe hypoglycaemia was more prevalent in minority ethnic groups and was not associated with SES. These findings are consistent with previous reports that children from ethnic minorities have higher HbA 1c levels in both the USA [2,13,30] and Europe [15,16]. However these differences have often been ascribed to differences in SES [2,18].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Ethnicity had a greater impact than SES on HbA 1c , and moderate to severe hypoglycaemia was more prevalent in minority ethnic groups and was not associated with SES. These findings are consistent with previous reports that children from ethnic minorities have higher HbA 1c levels in both the USA [2,13,30] and Europe [15,16]. However these differences have often been ascribed to differences in SES [2,18].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with previous reports that children from ethnic minorities have higher HbA 1c levels in both the USA [2,13,30] and Europe [15,16]. However these differences have often been ascribed to differences in SES [2,18]. In contrast, the present analysis strongly suggests that, although part of the effect is related to higher levels of deprivation, ethnicity makes a substantial direct contribution.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous research has suggested that African American and Hispanic youth are at risk for poor glycemic control while in pediatric care, although some studies have found that socioeconomic variables account for this effect. 7,17,18 Young adults from minority racial/ethnic backgrounds are considered at increased risk of poor transition outcomes. 19 Given our findings, this warrants further evaluation in future studies.…”
Section: Discussionmentioning
confidence: 99%